ANALISIS PENGENDALIAN KUALITAS KOPIKO CAPPUCINO MENGGUNAKAN METODE SIX SIGMA DMAIC PADA AREA DEPOSITOR DI PT MAYORA INDAH TBK - Ossa Sutaarga; Farid Amiza (Journal Industrial Manufacturing, 2025)
Mayora Indah Tbk is a company that produces various kinds of processed foods and beverages, one of which is Kopiko Cappuccino. Problems that arise in the production process still produce defective products, one of which is in the depositor work area. One method that can be used is to use the DMAIC method, the selection of the DMAIC method because many studies have proven that the DMAIC method can reduce DPMO and increase the production sigma level. From the data obtained from January to March 2025, there are three main types of defects in Kopiko Cappuccino products, namely nude sepet defects, incomplete nude defects, and double nude defects as much as 83.18% of the total defects that occur. These three types of defects are analyzed using a fishbone diagram with five main factors, namely machines, humans, materials, environment, and methods. Before the improvement, the DPMO value was 3620 for one million production, the sigma level was 4.18. Methods to control product defects in the depositor section include conducting improvement activities, creating a training schedule for workers, maintaining and repairing machines, creating depositor control forms, maintaining work area cleanliness, improving product monitoring, and modifying equipment. After improvements in June 2025, the sigma value was 4.34 and the DPMO was 2247.